2-Oxaspiro[4.5]decane and α-pyrenocine derivatives from the endophytic fungus Roussoella sp. PSU-H51. Issue 19 (21st September 2022) - Sommart, Ubonta; Rukachaisirikul, Vatcharin; Saithong, Saowanit; Phongpaichit, Souwalak; Sakayaroj, Jariya; Preedanon, Sita; Chainok, Kittipong; Khunrong, Teerayut
Abstract: One new 2-oxaspiro[4.5]decane, roussoellide, and one new α- pyrenocine, 2 ', 3 ' -dihydropyrenocine A, together with nine known compounds including known arthropsolide A, and pyrenocines A and E, were obtained from the culture broth of the endophytic fungus Roussoella sp. Their structures were determined using spectroscopic data. The absolute configuration of known arthropsolide A was assigned on the basis of X-ray diffraction data using Cu K α radiation. Known pyrenocine A displayed weak cytotoxic activity against breast cancer (MCF-7) cells with an IC50 value of 27.1 µ M and weak antifungal activity against Microsporum gypseum SH-MU-4 with an MIC value of 615.2 µ M.